Pengaruh Dana Bagi Hasil, Dana Alokasi Umum, dan Dana Alokasi Khusus terhadap Indeks Pembangunan Manusia di Provinsi Nusa Tenggara Timur - Ina, Yovita Tamo; Hudang, Adrianus Kabubu (Jurnal Ilmiah Global Education, 2024)
Improving the Human Development Index (HDI) is not directly aimed at boosting the economy, but rather at improving the overall quality of human life. This study aims to analyse the effect of Revenue Sharing Funds (DBH), General Allocation Funds (DAU), and Special Allocation Funds (DAK) on the HDI in East Nusa Tenggara (NTT). This study uses a descriptive statistical analysis method with the help of the EViews 10 analysis tool. The study found that partially, the DBH and DAK variables have a positive effect on the HDI. This means that an increase in these variables will increase the HDI. Meanwhile, DAU has a negative influence. This means that each increase in DAU will actually lower the HDI in NTT. Furthermore, simultaneously, the DBH, DAU, and DAK variables have a significant effect on the HDI in NTT.